Dynamic buckling of non-sway imperfect rectangular steel frames - RAFTOYIANNIS, I. G.; KOUNADIS, A. N. (Engineering Transactions, 2009)
A nonlinear stability analysis is performed on non-sway rectangular two-bar steel frames subjected to a concentrated, suddenly applied joint load with constant magnitude and infinite duration. Using energy and geometric considerations, the dynamic buckling load is determined by considering the frame, being a continuous system, as a discrete 2 degrees-of-freedom system with corresponding coordinates of the two bar axial forces. The effect of imperfection sensitivity due to loading eccentricity is also addressed. A qualitative and quantitative analysis of these autonomous systems yields a substantial reduction of the computational work. The efficiency and reliability of the nonlinear stability analysis proposed herein is illustrated by several examples, which are also solved using finite element nonlinear analysis.